Psychotropic and Opioid-Based Medication Use among Economically Disadvantaged African-American Older Adults - Bazargan, Mohsen (Pharmacy (Basel), 2020)
African-American older adults, particularly those who live in economically deprived areas, are less likely to receive pain and psychotropic medications, compared to Whites. This study explored the link between social, behavioral, and health correlates of pain and psychotropic medication use in a sample of economically disadvantaged African-American older adults. This community-based study recruited 740 African-American older adults who were 55+ yeas-old in economically disadvantaged areas of South Los Angeles. Opioid-based and psychotropic medications were the outcome variables. Gender, age, living arrangement, socioeconomic status (educational attainment and financial strain), continuity of medical care, health management organization membership, sleeping disorder/insomnia, arthritis, back pain, pain severity, self-rated health, depressive symptoms, and major chronic conditions were the explanatory variables. Logistic regression was used for data analyses. Arthritis, back pain, severe pain, and poor self-rated health were associated with opioid-based medications. Pain severity and depressive symptoms were correlated with psychotropic medication. Among African-American older adults, arthritis, back pain, poor self-rated health, and severe pain increase the chance of opioid-based and psychotropic medication. Future research should test factors that can reduce inappropriate and appropriate use and prescription of opioid-based and psychotropic medication among economically disadvantaged African-American older adults.